Perceived uncivil behaviour in Indonesian nursing education. (September 2016) - Eka, Ni Gusti Ayu; Chambers, Derek; Narayanasamy, Aru
Abstract: Uncivil behaviour is a phenomenon that has attracted a growing number of investigations, particularly in Western based nurse education. Unlike the West, uncivil behaviour is a relatively new field of study to Indonesia. However, with the incidence of incivility becoming a growing problem within Indonesian nurse education it is one that warrants investigation. This study investigated; the construct of uncivil behaviour and how it is perceived by students and faculty within the Indonesia context. The impact that socio economic status may play in its manifestation is also explored. The study was conducted in two faculties of nursing in the west of Indonesia. Findings suggest that religion is strongly implicated in the way that uncivil behaviour is perceived.